Turbulence and mixing variability in a microtidal estuary subject to mixed semidiurnal tidal cycles - Tiede, Jan; Cossu, Remo; Visscher, Jan; Grinham, Alistair; Schlurmann, Torsten (Frontiers in Marine Science, 2025)
Reynolds stresses and Turbulent Kinetic Energy (TKE) are instrumental in quantifying the turbulent dynamics that govern mixing and momentum transport in estuaries, factors crucial for understanding and managing estuarine circulation, water quality, and sediment transport. Employing Acoustic Doppler Current profilers, this study investigated hydrodynamics and turbulence in the Brisbane River, Australia. Measurements were conducted at two locations, covering the mouth and middle reach of the estuary. Of particular interest were flow reversals during flood flows, adding complexity to the turbulent dynamics. Reynolds stresses at site I were primarily generated by bed shear, while site II showed more complex stresses due to density differences and lateral circulations. At the river mouth, the mixed semidiurnal tidal regime led to a highly variable turbulent regime, with subsequent flood and ebb events exhibiting markedly different characteristics.